2016
DOI: 10.3109/15569527.2015.1127255
|View full text |Cite
|
Sign up to set email alerts
|

Clinical progression of ocular injury following arsenical vesicant lewisite exposure

Abstract: Ocular injury by lewisite (LEW), a potential chemical warfare and terrorist agent, results in edema of eyelids, inflammation, massive corneal necrosis, and blindness. To enable screening of effective therapeutics to treat ocular injury from LEW, useful clinically-relevant endpoints are essential. Hence, we designed an efficient exposure system capable of exposing up to six New-Zealand white rabbits at one time, and assessed LEW vapor-induced progression of clinical ocular lesions mainly in the cornea. The righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…A recent study was performed in a rabbit model for the screening of effective therapeutics to treat ocular injury and to develop clinically relevant end points. Ocular injury caused by Lewisite resulted in edema of the eyelids, inflammation, massive corneal necrosis, and blindness, which was similar to that reported in humans . The single vapor exposure of Lewisite to the eye of New Zealand white rabbits induced clinical ocular lesions, mainly in the cornea.…”
Section: Chemical Warfare and Industrial Arsenicalssupporting
confidence: 77%
See 1 more Smart Citation
“…A recent study was performed in a rabbit model for the screening of effective therapeutics to treat ocular injury and to develop clinically relevant end points. Ocular injury caused by Lewisite resulted in edema of the eyelids, inflammation, massive corneal necrosis, and blindness, which was similar to that reported in humans . The single vapor exposure of Lewisite to the eye of New Zealand white rabbits induced clinical ocular lesions, mainly in the cornea.…”
Section: Chemical Warfare and Industrial Arsenicalssupporting
confidence: 77%
“…These alterations were associated with neovascularization, which could be visualized at day 7, peaked between days 22 and 35, and remained persistent thereafter. Lewisite also caused corneal thickness, iris redness, and redness and swelling of the conjunctiva …”
Section: Chemical Warfare and Industrial Arsenicalsmentioning
confidence: 98%
“…Unlike SM, LEW exposure results in an immediate irritation, inflammation of the eyes, and swelling of the eyelids . The findings from our recent study for the first time showed clinical sequelae of ocular injury following LEW exposure, including corneal wounding, ulceration, inflammation, neovascularization, corneal thickness, iris redness, and redness and swelling of the conjunctiva, and their progression up to 56 days postexposure . Importantly, LEW exposure in humans is shown to result in swelling and edema, inflammation to the iris and conjunctiva, and corneal damage; the injuries are similar to those observed in the rabbit model in our study, suggesting the relevance of the model developed by us for both mechanistic and efficacy studies in the future.…”
Section: Development Of Vesicant‐induced Ocular Injury Modelsmentioning
confidence: 60%
“…Importantly, LEW has not been studied as extensively as SM; therefore, useful end points are required for screening and development of effective therapies. Hence, in collaboration with MRIGlobal®, we have designed an efficient exposure system capable of exposing up to six rabbits at one time, with the ability to adjust both time and dose of vesicants . In this exposure system, the left eye of the rabbit serves as a control and is exposed to dilution air, while the right eye is simultaneously exposed to LEW or SM.…”
Section: Development Of Vesicant‐induced Ocular Injury Modelsmentioning
confidence: 99%
See 1 more Smart Citation